Data Analytics in the Football Industry: The Portuguese Football Federation Case - Cunha, Sofia Alexandra Grifo (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics